THE EFFECT OF NATURAL GUARD SUPPLEMENT IN BROILER DRINKING WATER ON THE HEALTH AND SAFETY OF THE LIVER, SPLEEN, AND KIDNEYS - Baadilla, Millaniladzim; Ardana, Ida Bagus Komang; Supartika, I Ketut Eli; Merdana, I Made Merdana; Luh Made Sudimartini (Buletin Veteriner Udayana, 2025)
The broiler industry in Indonesia has grown rapidly since the 1970s and has become a primary source of animal protein. However, the health of vital organs such as the liver, spleen, and kidneys plays a crucial role in broiler productivity. Natural Guard (NG) is a feed supplement claimed to benefit these organs, but research on its safety remains limited. This study aimed to evaluate the effect of NG supplementation through drinking water on the health of the liver, spleen, and kidneys in broilers. A completely randomized design (CRD) was used, with four treatment groups: control without NG (P0) and NG supplementation at 1 g/L (P1), 2 g/L (P2), and 4 g/L (P3). Histopathological analysis was performed using Hematoxylin-Eosin (HE) staining, and data were analyzed using the Kruskal-Wallis test. The results showed no necrotic lesions in any group, while congestion and inflammatory cell infiltration were observed at mild to moderate levels without significant differences (P>0.05). This indicates that NG supplementation up to 4 g/L does not cause harmful pathological changes in the liver, spleen, and kidneys of broilers. In conclusion, NG is safe to use as a feed supplement for broilers. Further research is needed to assess its long-term effects and impact on broiler productivity.